2021
DOI: 10.1111/jce.15221
|View full text |Cite
|
Sign up to set email alerts
|

Zero fluoroscopy approach versus fluoroscopy approach for cardiac arrhythmia ablations: A systematic review and meta‐analysis

Abstract: Background Radiofrequency catheter ablation for cardiac arrhythmias has traditionally been guided by fluoroscopy. Fluoroscopy exposes the patient, operator, and staff to ionizing radiation which has no safe dose void of stochastic and deterministic biologic risks. Zero fluoroscopy (ZF) approaches for catheter ablation have been advocated to eliminate these risks. We conducted a meta‐analysis comparing acute procedure success, recurrence‐free survival, complications, and procedure times between the approaches. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Although the sub‐analysis on the efficacy and safety of the ZF approach was not noted in the subgroup undergoing ablation for RVOT VAs, the study demonstrated that using 3D EAM for completely ZF approach is as safe and efficient as the fluoroscopy approach for the ablation of idiopathic VAs 11 . In a systematic review and meta‐analysis of ZF approach versus fluoroscopy approach for cardiac arrhythmia ablations published in 2021, the subgroup analysis of VAs ablation presented no significant differences in acute procedure success rate, recurrence‐free survival, periprocedural complication rate, or total procedural time between ZF and fluoroscopy approach 17 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although the sub‐analysis on the efficacy and safety of the ZF approach was not noted in the subgroup undergoing ablation for RVOT VAs, the study demonstrated that using 3D EAM for completely ZF approach is as safe and efficient as the fluoroscopy approach for the ablation of idiopathic VAs 11 . In a systematic review and meta‐analysis of ZF approach versus fluoroscopy approach for cardiac arrhythmia ablations published in 2021, the subgroup analysis of VAs ablation presented no significant differences in acute procedure success rate, recurrence‐free survival, periprocedural complication rate, or total procedural time between ZF and fluoroscopy approach 17 …”
Section: Discussionmentioning
confidence: 92%
“…11 In a systematic review and meta-analysis of ZF approach versus fluoroscopy approach for cardiac arrhythmia ablations published in 2021, the subgroup analysis of VAs ablation presented no significant differences in acute procedure success rate, recurrencefree survival, periprocedural complication rate, or total procedural time between ZF and fluoroscopy approach. 17 RVOT VAs are frequently idiopathic of origin. 1,2 However, some…”
Section: Safety and Efficacy Of Zero-fluoroscopy Ablation For Rvot Va...mentioning
confidence: 99%
“…15 The average effective dose is 3.2 mSv during EPSs and 15.2 mSv during catheter ablation, although this can be reduced to zero using EAMs. 14 In a recently published meta-analysis, Kanitsoraphan et al 16 found that zerofluoroscopic catheter ablation of arrhythmias is as effective and safe as conventional catheter ablation.…”
Section: Discussionmentioning
confidence: 99%
“…Переход из группы нефлюороскопической абляции в группу с применением рентгеноскопии был осуществлен только у 1,26 % пациентов. Согласно полученным результатам, не выявлено достоверного увеличения продолжительности процедуры без использования флюороскопии по сравнению со стандартной методикой (средневзвешенная разница 2,32 мин; 95 % доверительный интервал -ДИ -2,85-7,50), а также не регистрировались статистически значимые различия по частоте развития осложнений (отношение шансов -ОШ 0,72; 95 % ДИ 0,45-1,16), неэффективности процедуры (ОШ 1,10; 95 % ДИ 0,75-1,59) или рецидивов нарушений ритма [18].…”
Section: Discussionunclassified
“…Проведенные нами вмешательства без использования рентгеноскопии у 20 пациентов с ЖТ не сопровождались развитием клинически значимых осложнений, применения флюороскопии не потребовалось ни в одном случае. Использование ВС-ЭхоКГ позволило провести качественное картирование, и длительность процедуры существенно не отличалась от таковой при выполнении подобных вмешательств [18,19]. В приведенный выше метаанализ вошло всего 2 исследования, посвященных КА ЖТ, с участием 254 пациентов без использования флюороскопии и 369 -с флюороскопией.…”
Section: Discussionunclassified